Az 1919. évi felvidéki hadjárat geográfiai kérdései - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2011)
The months following the First World War brought social crisis and another armed conflict in Hungary. The Hungarian society, which was exhausted by the world war was forced into combat for the territorial integrity of the country, an important event of which was the offensive campaign carried out in Northern Hungary. During these efforts the Hungarians liberated significant territories but the international political situation did not make it possible for the Hungarian political leadership to turn the military success into diplomatic gains. This also caused the collapse of the communist dictatorship which seized power in Budapest on March 21, 1919. Although the Marxist literature of military history in the second half of the previous century dealt with this issue in detail, it could not focus on researching the military geographic and political background of the Northern Hungarian campaign for well known political and ideological reasons. This paper aims to present the constraints of this military campaign by analyzing the military geographic factors which influenced the campaign. On the basis of this it wishes to illustrate the issue of the political geographic surroundedness of the Hungarian dictatorial system by using the methodology of historical geography. It also attempts to overview the issue of Soviet Russian military assistance from a geographic perspective an aspect often mentioned by the Marxist ideology of the previous century, but something that was never actually realized. The designation of the main campaign direction, the later halting of the campaign for foreign policy reasons and finally the continuation of it in a direction that hardly promised any military results shows the conceptual changes of the Hungarian foreign policy leadership. The relationship between these adjustments and the changes in the foreign policy environment proves the connection between geographic, political and military factors amid specific Hungarian conditions.